2018
DOI: 10.1002/aoc.4726
|View full text |Cite
|
Sign up to set email alerts
|

Double stereoselective coordination of chiral N,S ligands: Synthesis, coordination chemistry and utilization in Pd‐catalyzed allylic alkylation

Abstract: A series of chiral pentane‐2,4‐diyl‐based thioether‐amine ligands [4 and 5; (R,S)‐ and (S,S)‐R1SCH(CH3)CH2CH(CH3)NHR2, respectively, where 4a R1 = iPr, R2 = Ph; 4b R1 = tBu, R2 = Ph; 4c R1 = 1‐Ad, R2 = Ph; 5a R1 = iPr, R2 = Ph; 5b R1 = tBu, R2 = Ph; 5c R1 = 1‐Ad, R2 = Ph; 5d R1 = iPr, R2 = 4‐MeOC6H4; 5e R1 = iPr, R2 = 4‐MeC6H4; 5f R1 = iPr, R2 = 3,5‐Me2C6H3] with stereogenic S‐ and N‐donor atoms has been prepared starting from cyclic sulfates via optically pure γ‐aminoalcohol or 2,4‐dimethylazetidine intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Heterodonor N,S/Se-ligands with a variety of donor group combinations (e.g., imine-thioether, oxazoline-sulfoxide, thiazoline-thioether) have also been studied. 339 351 In most cases, they provided only moderate enantioselectivities. As a notable exception, up to 98% ee was obtained with the simple amine-selenoether ligand L112 in the alkylation of rac -1,3-diphenylallyl acetate with dimethyl malonate ( Scheme 95 a).…”
Section: Asymmetric Allylic Substitutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterodonor N,S/Se-ligands with a variety of donor group combinations (e.g., imine-thioether, oxazoline-sulfoxide, thiazoline-thioether) have also been studied. 339 351 In most cases, they provided only moderate enantioselectivities. As a notable exception, up to 98% ee was obtained with the simple amine-selenoether ligand L112 in the alkylation of rac -1,3-diphenylallyl acetate with dimethyl malonate ( Scheme 95 a).…”
Section: Asymmetric Allylic Substitutionmentioning
confidence: 99%
“…Heterodonor N,S/Se-ligands with a variety of donor group combinations (e.g., imine-thioether, oxazoline-sulfoxide, thiazoline-thioether) have also been studied. In most cases, they provided only moderate enantioselectivities. As a notable exception, up to 98% ee was obtained with the simple amine-selenoether ligand L112 in the alkylation of rac -1,3-diphenylallyl acetate with dimethyl malonate (Scheme a). , Similar enantioselectivities were achieved using the ferrocene-based thiazoline-thioether ligands L113 and L114 (Scheme a). , X-ray and NMR spectroscopic studies of the π-allyl intermediates indicated that the sulfur atom was a stronger π-acceptor than the nitrogen atom.…”
Section: Asymmetric Allylic Substitutionmentioning
confidence: 99%
“…A stereogenic center is created at the sulfur atom upon coordination to the Rh center. [51][52][53][54] As a result, a mixture of diastereomers are present, (SC, RS) and (SC, SS), due to the sulfur stereogenic center and the S configuration at the asymmetric carbon on the bridging oxazolidinate (Figure 3). Of the four paddlewheel units, two are (SC, RS) and two structures are (SC, SS), with minor structural variations between them.…”
Section: Resultsmentioning
confidence: 99%
“…More broadly effective palladium catalysts for nucleophiles have also been determined over the years (Yang et al, 2015(Yang et al, , 2016Jiang et al, 2017). Recently, it has been reported that the chirality of catalytic ligand could significantly influence the stereoselective coordination (Major et al, 2019). In consideration of the enormous raw reactants and catalysts mentioned above, the mechanism of the high enantioselectivity for the N-alkylation reaction still needs further elaboration.…”
Section: Introductionmentioning
confidence: 99%